KELOLA LINGKUNGAN MELALUI EDUKASI BUDIDAYA AQUAPONIK & HIDROPONIK SEBAGAI ALTERNATIF SOLUSI UNTUK MEMANFAATKAN LAHAN BAGI MASYARAKAT DESA PERLANG BANGKA BELITUNG - Erika Fitri Wardani; Hendi Hedra Bayu; Lulu Ul Karimah; Lindawati Lindawati; Muhammad Lanza Pahlevi (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Perlang village is one of the villages in the Lubuk Besar sub-district, Central Bangka district, Bangka Belitung archipelago province. Perlang Village has rich and diverse natural resources. From interviews with village officials, information was obtained that some Perlang village lands store a wealth of tin sources, the majority of Perlang village people work as active miners. This is in line with the observation that several former lands were found. Mining excavations are holes filled with water. This activity is a type of community service activity that is integrated with KKN, the team implementing this activity consists of field supervisors, expert lecturers, and students who carry out KKN. The purpose of this activity is to provide education to the Perlang village community about how to manage and utilize the environment through aquaponic and hydroponic cultivation. The method used in this activity is the delivery of material through lectures, question and answer with the help of power point media. This activity has been running smoothly and well, the results of the activity showed that the community was enthusiastic about participating in the ongoing activities by asking questions to the presenters and the community also felt that they were given new insights. With this activity, it is hoped that the community will be able to independently or jointly innovate in modern agriculture with aquaponic or hydroponic cultivation as a form of utilizing increasingly limited land and as a form of anticipation in the future if the tin mining products run out they can switch to modern agriculture.